EVALUASI KINERJA UNIT CRUSHING PLANT JAQUES UNTUK MENINGKATKAN PRODUKSI GRANIT DI PT. TRIMEGAH PERKASA UTAMA KABUPATEN KARIMUN KEPULAUAN RIAU - Riki Adha; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT Trimegah Perkasa Utama is a granite manufacturer in Indonesia. Granite is processedusing a crushing plant. Based on split stone production data at PT Trimegah Perkasa Utama in July2018, the company's granite stone production target of 180,000 tons / month was not achieved. Whilethe actual production obtained was 141,114 tons / month or 87.51% of the production target. This isdue to the many disruptions to repair and standby times during the processing of granite stones anddamage to the jaw crusher, so that from these disturbances the effective working time is reduced. Theresults obtained after repairing are reduction in repair time and standby time so that the primarycrusher's effective working time becomes 219.53 hours, 38.85% work efficiency and secondary andtertiary crusher's effective working time to 311.58 hours, work efficiency 53.72%. The value of crushingplant unit availability will also increase. Primary crusher unit production increased to 162,000 tons /month after increasing effective working time. Production of secondary and tertiary crusher units canbe increased by setting the gyratory crusher closed side setting to 71 mm and the cone crusher to 23mm.Keywords: Crushing Plant, Granite, Jaw Crusher, Production, Repair Time